FINANCE RULES IN CONDITIONS OF MACRO-ECONOMIC UNCERTAINTY - Vladimir A. Slepov; Albert F. Arslanov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article provides some authors’ considerations about usefulness of rules in the finance field, which is characterized by scholasticism and uncertainty. The authors give their interpretation of the term ‘finance rules’, analyze the current condition of the global finance system and show challenges of its development. The article discusses key global finance instruments for adaptation of finance systems to growing uncertainty of the macro-economic environment. Principle attention is paid to rules accumulated by certain countries in the field of monetary and credit and budget policy. Their advantages in comparison with discretionary, sporadic steps of regulation bodies were demonstrated. The combined use of finance rules in today’s condition is necessary to provide their efficiency. Coordination of finance rules in monetary and credit and budget policy is shown as the authors’ economic-mathematic model.